2011
DOI: 10.1007/s13530-011-0072-7
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of nano-silica in mammalian cell lines

Abstract: Nanomaterials are defined by the U.S. National Nanotechnology Initiative as materials that have at least one dimension in the 1-to 100-nm range. Due to their unique physical and chemical characteristics, nanotechnology has become one of the leading technologies over the past 10 years. This study represents data on genotoxic effects of nanoparticles and their application for assessing human health risks. Silica (SiO 2 ) is a multi-functional ceramic material that is being used in various industries to improve s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 31 publications
2
12
0
1
Order By: Relevance
“…[199] Additionally, hypomethylation of DNA was found after the treatment of human keratinocytes (HaCaT) with SiO NPs. [200] Jin et al observed that luminescent SiO NPs induced an increase in hOgg1 enzyme (related to DNA repair) expression, but no change in enzyme activity in A549 cells.…”
Section: Genotoxicity Of Sio Particlesmentioning
confidence: 99%
“…[199] Additionally, hypomethylation of DNA was found after the treatment of human keratinocytes (HaCaT) with SiO NPs. [200] Jin et al observed that luminescent SiO NPs induced an increase in hOgg1 enzyme (related to DNA repair) expression, but no change in enzyme activity in A549 cells.…”
Section: Genotoxicity Of Sio Particlesmentioning
confidence: 99%
“…Even though the majority of the studies have reported negative results for the genotoxicity of SiO 2 , 11,17,47 a few investigations have indicated otherwise. 49 Downs et al investigated the genotoxic effects of exposure to three consecutive intravenous injections of SiO 2 nanoparticles by in vivo comet assay in rat liver and lung tissues, and observed the induction of DNA damage by SiO 2 . 50 Hence, the different administration route can lead to different results for genotoxicity evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The cyto and genotoxicity of functionalized Si-NPs with different charge on Eisenia fetida coelomocytes is not reported. Choi, et al [10] studied the cyto and genotoxicity of Si-NPs in mammalian cell lines, using the dye exclusion, comet, and mouse lymphoma assays. Authors reported an inhibition concentration for 20% of the assayed L5178Y and BEAS-2B cell populations (IC20) of Si-NPs, ranged between 2.441-2.363 mg/mL, 2.324-0.537 mg/mL, respectively.…”
Section: Methodsmentioning
confidence: 99%